Evaluation of DNA barcode abiotic surrogate as a predictor for inactivation of E. coli O157:H7 during spinach washing. (June 2021) - Bolten, Samantha; Gu, Ganyu; Gulbronson, Connor; Kramer, Matthew; Luo, Yaguang; Zografos, Antonios; Nou, Xiangwu
Abstract: Fresh-cut leafy greens are washed in water with antimicrobials such as free chlorine to mitigate risk of pathogen cross-contamination. Validation of the process in a commercial setting poses challenges, including the identification of effective surrogates that can be used directly on the processing line during commercial operation. The objective of this study was to evaluate the use of an abiotic, DNA-based indicator as a potential surrogate for Escherichia coli O157:H7 during the washing of spinach. E. coli O157:H7 and DBAS (DNA barcode abiotic surrogate) were inoculated onto spinach leaves and washed in water with free chlorine. E. coli O157:H7 and DBAS populations were enumerated by selective plate counting or qPCR, respectively, and by laser scanning confocal microscopy. DBAS displayed high sensitivity to free chlorine at concentrations ≥12.5 mg/L, similar to concentrations commonly used in leafy green washing. Linear regression analysis indicated that inactivation of E. coli O157:H7 and DBAS had comparable inactivation responses ( R 2  = 0.76). Microscopy analysis also showed similar rates of decontamination between the two analytes from the surface of spinach. These results show that DBAS is a promising abiotic surrogate for onsite validation of antimicrobial processes targeting foodborne pathogens such as E. coli O157:H7 on fresh produce. Highlights: A GRAS substance with embedded DNA was tested as abiotic surrogate for foodborne pathogen. This DNA-based abiotic surrogate (DBAS) showed comparable adhesion on spinach as an E. coli O157:H7 strain. DBAS and E. coli O157:H7 strain showed comparable inactivation when treated in chlorinated water.